1999
DOI: 10.1016/s1085-5629(99)80018-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioral dermatitis in children

Abstract: Perioral dermatitis is a unique skin disorder of childhood. Its exact origin is unknown; it is probably an idiosyncratic response to exogenous factors such as the use of a topical fluorinated corticosteroid or other substances on the face. It is uncommon but not rare. The age of affected children has ranged from 7 months to 13 years, with the median being in the prepubertal period. Boys and girls, blacks and whites are equally affected. Clinical features include the following: (1) absence of systemic symptoms;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
0
23
0
2
Order By: Relevance
“…POD was initially termed “light‐sensitive seborrheid” and became known as POD several decades later based on the characteristic papulopustular eruption around the mouth, nose, and eyes . Histologic examination is rarely performed but displays epithelioid cells and lymphohistiocytic infiltrate with occasional giant cells, indistinguishable from rosacea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POD was initially termed “light‐sensitive seborrheid” and became known as POD several decades later based on the characteristic papulopustular eruption around the mouth, nose, and eyes . Histologic examination is rarely performed but displays epithelioid cells and lymphohistiocytic infiltrate with occasional giant cells, indistinguishable from rosacea .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric periorificial dermatitis (POD) is a common but underreported chronic facial rosacea‐like eruption located around the mouth, nose, and eyes. Since 1957, 90% of POD cases have been described in young adult women . However, pediatric POD has been reported in children as young as 6 months of age, with most cases in children younger than 5 years old .…”
mentioning
confidence: 99%
“…3 While topical corticosteroids play a part in adult perioral dermatitis, they usually do not in children, adding support for differentiating between adult and childhood disease. Periorificial dermatitis in adults is in most cases precipitated by the use of topical corticosteroids on the face.…”
Section: Discussionmentioning
confidence: 99%
“…These studies emphasise the association of recurrent chalazia with rosacea in children. Periorificial dermatitis is not uncommon in children and, while some consider it to be a separate entity to and differential diagnosis for rosacea, 1,2 some studies have found close associations linking periorificial dermatitis to childhood rosacea 3 and, in particular, ocular signs of rosacea. 4 There are no clear guidelines for first-line therapy in childhood rosacea.…”
Section: Introductionmentioning
confidence: 99%
“…This drug is used both systemically and topically for certain skin diseases (2, 4). Its effectiveness in treating rosacea, dermatitis perioralis, as well as acne inflammation, probably by inhibiting oxidative tissue injury in the presence of palmitoleic acid, has been reported (5, 6).…”
Section: Introductionmentioning
confidence: 99%